Karakteristik biopelet tempurung kelapa dan serbuk kayu sebagai bahan bakar alternatif - Suyoko, Muhammad; Ridhuan, Kemas; Dharma, Untung Surya (Universitas Muhammadiyah Metro, 2020)
Biomass is a solid waste derived from biological material that can be generated as fuel. Biomass includes plantation, agriculture, household, forest waste and waste from the wood industry, one of the uses of biomass is bio-pellet. Bio-pellet is an alternative type of energy in the form of solid fuel made from biomass raw material with a size smaller than the size of briquettes. In this research, raw materials from teak wood, acacia, and sengon wood powder were used as well as a mixture of coconut shell charcoal with tapioca adhesive. This study aims to determine the bio-pellet estimation analysis, determine the heating value required by the bio pellet in the combustion process, and determine the burning characteristics of the three types of bio pellets. The method used in this study was the process of making bio-pellet with the same treatment on each bio-pellet, variations bio pellet will be made is 50% teak wood powder and 50% coconut shell charcoal powder, 50% acacia wood powder and 50% coconut shell charcoal powder, and 50% sengon wood powder and 50% coconut shell charcoal powder. Each bio pellet uses an adhesive mixture of 5% of the raw material. The stages of the testing process are bio pellet in laboratory tests to determine the value of the composition of the levels of heat, water, ash, flying substances, and bound carbon. The next testing process is the testing process of bio pellet combustion using a bio pellet stove with a process of boiling 10 liters of water, with fire temperature, water temperature, and the remaining fuel measured. All was done at UM Metro 2 campus. The results of bio pellet testing in the laboratory stated that the highest value was in sengon bio pellet with heating value of 5815.19 cal/g, water content of 5.82%, the ash content of 9.77%, levels of flying matter 69.37%, and carbon content bound 19, 41%. For the high heating value of bio pellet burning is 784.92 kcal/hour. Then the best efficiency is the sengon bio- pellet with a value of 55%.